ANALYSIS OF MENTAL NURSING CARE FOR TN.R WITH SENSORY PERCEPTION DISORDERS: AUDITORY HALLUCINATIONS WITH THE IMPLEMENTATION OF DISTRACTION TRAINING IN CONVERSATION AND SCHEDULED ACTIVITIES IN THE SIGMA ROOM OF JAMBI PROVINCE RSJD IN 2023 - Siringo-ringo, Fajar Pandapotan; Nasution, Riska Amalya (Jurnal Pinang Masak, 2023)
Mental disorder is a psychological problem or clinical behavior pattern, which occurs in individuals and is associated with distress, disability or is accompanied by a significant increase in risks such as loss of independence, disability, causing illness or even loss of life. The prevalence of severe mental disorders such as schizophrenia reaches around 400,000 people or around 1.7 per 1,000 population. Hallucination sensory perception disorder is one of the main symptoms and most commonly found in clients with schizophrenia. Hallucinations are a symptom of mental illness in which the client experiences sensory changes and perceives false sensations in the form of sounds, images, tastes, touches, smells. The results of the study found that the patient had entered the RSJ for the third time and the patient said that while in the RSJ he only knew about rebooking and did not know the act of conversing and scheduled activities. Writing the final scientific work of nurses aims to analyze the implementation of nursing care in patients with sensory perception disorders: auditory hallucinations using the application of conversational distraction exercises and scheduled activities. The results of this scientific work showed a decrease in signs and symptoms of hallucinations after successfully achieving all the evaluation criteria for conversations and scheduled activities. This application can be used as teaching material for the development of knowledge about sensory perception disorders: auditory hallucinations.